Prospect of Sugar Palm Agro-Industry - ABNER LAY; BAMBANG HELIYANTO (Perspektif, 2011)
Palm juice is the economic product of sugar palm tree. Traditionally sugar processing technology is found in sugar and alcohol processing units. Innovative technology is found in brown sugar, crystal sugar, palm wine, and absolute alcohol or ethanol an-hydrate.  Determinants of sugar palm agro-industry develop-ment consist of empowerment of farmers, processing technology, funding/investment, product development and marketing.  Future sugar palm agro-industry may follow agro-industrial model by Hariang-Banten and Masarang-Tomohon, with the orientation on high economic value products and based on broad and sustainable market. Keywords: Arenga pinnata, palm juice, sugar palm products, palm sugar agro-industry model